PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWTOON UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS IV SD - Riza Amanda; Umar Darwis (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to (1) increase student interest in science subjects in class IV SD (2) produce Powtoon-based learning media that is feasible to be developed in science subjects class IV SD. This research is a type of R&D (Research and Development) development research using the ADDIE model which includes 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. But this research is only up to three stages, namely only up to the Development stage. The subjects in this study were material expert validators, media expert validators, learning experts (grade IV teachers). The instrument used to collect data is a questionnaire or questionnaire. The data analysis technique used in this study is quantitative data in the form of scores from research via questionnaires. This quantitative data analysis technique in the validation process is carried out in the form of numbers with a Likert scale score reference. Based on the analysis of data obtained through the material validation test, media expert and teacher response, the results of the material expert validation, namely a score of 84, are included in the good/decent category, the results of the media expert validation, namely a value of 84, are included in the good/decent category, and the response of class IV teachers is a value of 94 is included in the good/decent category. based on the percentage of material experts, media experts, and the response of the class IV teacher, then the average score was obtained with a score of 87.3 included in the very good/very suitable category for use in the learning process